2019
DOI: 10.1016/j.chemphyslip.2018.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of ionised steryl esters with ozone in the gas phase

Abstract: Cholesterol is an ubiquitous membrane lipid, that also serves as a precursor to many steroid hormones. The 5,6 carbon-carbon double bond on the tetracyclic carbon backbone of cholesterol is an attractive target for ozone with the reaction giving rise to a wide range of possibly bioactive molecules. Despite this, little is known about the ozonolysis of cholesterol esters, which often possess an additional double bond(s) on the fatty acyl chain. Understanding the intrinsic gas phase reaction of ozone with the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 48 publications
0
9
0
1
Order By: Relevance
“…24 In this work, we show that ozone-induced cleavage of steroid endocyclic CC double bonds results in a ring opening that produces unique, energetically stable gas-phase conformations. Hancock et al recently demonstrated that OzID could be used to react endocylic CC double bonds in steryl esters; 25 however, the analytical utility of that observation was limited due to a lack of ion mobility separation. In this work, we demonstrate efficient IMS separation in a model steroid epimer pair, testosterone and epitestosterone, following ozone-induced cleavage of their endocyclic CC double bond.…”
mentioning
confidence: 99%
“…24 In this work, we show that ozone-induced cleavage of steroid endocyclic CC double bonds results in a ring opening that produces unique, energetically stable gas-phase conformations. Hancock et al recently demonstrated that OzID could be used to react endocylic CC double bonds in steryl esters; 25 however, the analytical utility of that observation was limited due to a lack of ion mobility separation. In this work, we demonstrate efficient IMS separation in a model steroid epimer pair, testosterone and epitestosterone, following ozone-induced cleavage of their endocyclic CC double bond.…”
mentioning
confidence: 99%
“…Atomistic modeling has shown that liquid-phase cholesteryl oleate exists on a spectrum of folded to unfolded ensembles, with the greatest flexibility being present between carbons 3 and 5 on the acyl chain (67). In previous work, we determined that an interaction exists between the site of charge localization on the carbonyl and both the endocyclic and acyl carbon-carbon double bonds in cholesteryl oleate that potentially aids folding of the structure in the gas phase, resulting in a smaller CCS and enhanced ion mobility (68). Therefore, it stands to reason that the distance between the sterol head group and double bond may also affect the folding of the steryl ester in the gas phase, with elongated distances between the sterol and double bond resulting in compact structures when the double bond is located >15 carbons from the carboxylate moiety.…”
Section: Discussionmentioning
confidence: 96%
“…While IMR remain a fairly “niche” technique, undoubtedly due to the requirements for often‐undesirable instrument modifications and reaction time penalty compared to other tandem MS techniques, some areas have clearly benefited from the technique. On the analytical side, the OzID technique pioneered by the Blanksby group for fatty acids and lipid analysis has been very successful (Bhujel et al, 2020; Hancock et al, 2019; Khairallah et al, 2015; Marshall et al, 2014, 2016, 2019, Paine et al, 2018; Pham et al, 2014; Poad et al, 2011, 2017; Thomas et al, 2007), especially with the rapid development of lipidomics. Recent advances include incorporation of liquid chromatography, ion mobility and imaging creating very powerful applications with unmatched capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Work done by Blanksby and coworkers explored the potential use of OzID on steryl esters. It revealed that endocyclic double bonds are far more reactive to those on the unsaturated acyl chain (Hancock et al, 2019).…”
Section: Siegelmentioning
confidence: 99%